Titanium, zirconia, and polyetheretherketone (PEEK) as a dental implant material - Khurshid, Zohaib; Hafeji, Saudah; Tekin, Samet; Habib, Syed Rashid; Ullah, Rizwan; Sefat, Farshid; Zafar, Muhammad Sohail (Elsevier, 2020)
Titanium (Ti) is one of the commonly used material for fabricating dental implants. Titanium has good corrosion resistance, low-elastic modulus, biocompatibility, and osteogenic potential. It has a low wear and abrasion resistance and this property overcome by treatment of Ti surface or coatings of other biomaterials such as hydroxyapatite, zirconia, and polyetheretherketone (PEEK). The present chapter describes various properties of Ti as dental implant materials including its interaction with oral tissues and osseointegration. In addition, Ti’s surface modifications and surface treatments to improve the properties have been discussed including zirconia and PEEK as dental implant coating materials. © 2020 Elsevier Ltd.
Keywords: Biomaterials; Dental implants; Polyetheretherketone (PEEK); Titanium; Zirconia